INFLUENCE OF WASTE GLASS POWDER ON THE PROPERTIES OF CONCRETE - Karpe Sambhaji Laxman; Jagtap Sunny Ashok; Jagtap Sunny Ashok (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Concrete is most widely used construction materials. However, the production of Portland cement releases significant amount of CO2, a greenhouse gas. One ton of Portland cement clinker production releases approximately one ton of CO2 and other greenhouse gases. Environmental issues are playing vital role in the sustainable development of concrete industry. Today many researches are ongoing for the replacement of Portland cement, using many waste materials like fly ash and ground granulated blast furnace slag (GGBS). Like Fly ash and GGBS a waste glass powder can also use as a binder with the partial replacement of cement which take some part of reaction at the time of hydration. Cement replacement by glass powder in the range 5% to 25% with an interval of 5% is to be study.It was tested for compressive strength, flexural strength and Split tensile strength at the age of 7, 28 days and compared with the results of conventional concrete. The overall test results shows that Waste Glass Powder could be used in concrete as a partial replacement of cement.